Parametric Study of a Hybrid Renewable Energy Power Generation System in the Colombian Caribbean Region (2022)
The global environmental problems have increased the interest in renewable energies, in this article a wind-solar hybrid system is proposed as an alternative for energy production. To carry out this study, the research was divided into three stages, the first one consists of determining the behavior of a solar and wind system, the second stage focuses on determining the ideal location to implement the hybrid system and the third stage determines the composition of wind and PV devices that offers greater efficiency. After completing the three stages proposed above, the optimal locations for the implementation of a wind-solar hybrid system are Simón Bolívar and Puerto Bolívar.